Development of friction stir spot welding windows for dissimilar Al5086/C10100 spot joints. (2018) - Siddharth, S.; Senthilkumar, T.
Abstract: In this paper, an attempt was made to develop process operation limit diagrams in the form of friction stir spot welding windows for obtaining good quality dissimilar Al 5086/ C10100 joints. The two dissimilar 1.5 mm thick plates were friction stir spot welded using non-consumable tool made of H13 material. The variations of tool rotational speed with dwell time at constant plunge depths were used for constructing the first window and variation of tool rotational speed with plunge depth at constant dwell time were considered for the second. Using a central composite design model, empirical relationships were developed for predicting the variations in tensile strength and interface hardness with changes in the friction stir spot welding process parameters. ANOVA analysis was used to evaluate the significance of the developed model at a confidence level of above 95%. Optimization of the friction stir spot welding process parameters were done using response surface methodology, by constructing surface and contour plots. Validation experiments were used to evaluate the developed model. The difference in the predicted values of the optimized model and actual experiments was less than 5%. Friction stir spot welding windows developed, can act as reference maps for future design engineers to achieve better spot joints.